Narrative Technique of Thai Historical Telenovelas - Jirabovornwisut, Sorarat; Akarachantachote, Preeda (Siam Communication Review, 2022)
A qualitative study of narrative technique in Thai historical telenovelas is aimed to study the reviving of the Thai historical telenovelas’ contents within the collective memory framework in 22 Thai historical telenovelas, 31 versions, during the 1988 - 2019. The research reveals that contents on collective memories are divided into five narrative patterns: glorification of the monarchy, golden age of Ayutthaya Kingdom, wars and peace, ideology beyond personal love, and time-travel; that many stages of the creative process are applied in the construction and communication, where the concept of nationalism or royal nationalism and the capital-centered perspective are mostly embraced. According to the study, collective memory in Thai historical telenovelas tends to reproduce the image of the monarchy that is deemed sacred, divine, and reign in righteousness within the national historical framework or grand narrative, as well as key concepts and values that are controlled by the State to emphasize the ideology of loyalty and sustain the power of the elites in the society.